Moderating effect of asean free trade agreement between total quality management and business performance - Ahmad, M.F.; Zakuan, N.; Jusoh, A.; Yusof, S.M.; Takala, J. (Elsevier, 2014)
The unprecedented pace of globalisation, trade liberalisation, and capital movement in the later years profoundly changed to pose serious challenges for Malaysian companies to compete in an open market. In today's highly competitive market, the demand for quality is important factor for companies to survive in the ever-expanding global marketplace. The concept of Total Quality Management (TQM) has been developed as a result of intense global competition. ASEAN trade liberalisation through the elimination of intraregional tariffs contributed to improving manufacturing in ASEAN countries to be more efficient and competitive in world markets. However, Asean Free Trade Agreement (AFTA) is a good news for foreign companies as they have competitive advantages, but not for local companies. The examining of AFTA as a moderator is less done in previous work. The purpose of this paper is to propose relationship between TQM practices and business performance with moderator effects of AFTA. The main contribution of this paper is to examine whether AFTA has the effect as a moderator. This proposed conceptual model will help the academicians and industry players to have better understanding on the effect of AFTA in TQM implementation in improving their business performance. The structural equation modeling (SEM) techniques are used to examine the relationships of the practices.
Keywords: total quality management (TQM); AFTA; business performance; structural equation modeling (SEM); enterprises; quality management (leadership); leadership (activity); quality management; quality; self-evaluation; organisations (systems); business; quality awards; success; fi=Tuotantotalous|en=Industrial Management|